The Association of Spanish Language Preference with Advance Directive Completion. Issue 1 (10th September 2020) - Gonzalez, Ruben; Lyon, Liisa; Rabbani, Juleon; Conell, Carol; Postlethwaite, Debbie; Spaulding, Mira; Mason, Michael
Abstract : BACKGROUND/OBJECTIVES: Hispanics have lower advance directive (AD) completion than non‐Hispanic Whites. Few studies have assessed the role of language preference in end‐of‐life planning. We investigated whether language preference and needing an interpreter affected AD completion among older adults in an integrated health system. DESIGN: Retrospective cohort investigation of electronic medical records. SETTING: Northern California integrated health system. PARTICIPANTS: A total of 620, 948 Hispanic and non‐Hispanic White patients, aged 55 years and older, between January 1, 2013, and December 31, 2017. MEASUREMENTS: Descriptive statistics and bivariate analysis were performed to compare AD completion among non‐Hispanic Whites, Hispanics, and Hispanic subgroups by language preference (English speaking, Spanish speaking, and needed interpreter). We conducted multivariable logistic regression to determine the relationship between language preference and having an AD while controlling for demographic, clinical, and utilization factors. RESULTS: We found 20.3% of non‐Hispanic Whites (n = 512, 577) and 10.9% of Hispanics (n = 108, 371) had completed an AD. Among Hispanics, after controlling for demographic, clinical, and utilization factors, compared with Spanish speakers requiring an interpreter, English speakers had nearly two‐fold increased odds of completing an AD (adjusted odds ratio (aOR) = 2.6; 95% confidence interval (CI) = 2.4–2.9), whereas Spanish speakers not requiring an interpreter had 20% increased odds (aOR = 1.2; 95% CI = 1.1–1.3). Additional predictors of successful AD completion were being female, being older, having more comorbidities, having more hospital and emergency department visits, and having higher socioeconomic status. There were no differences associated with primary care provider characteristics. CONCLUSION: These findings indicate the need for a tailored outreach to Hispanics, particularly among those subgroups who require the need of an interpreter, to reduce AD completion disparities.